Comparison of the energization of self-consistent charged particles vs test particles in a turbulent plasma - Pugliese, Facundo Leonel (2025)
The test particle approach is a widely used method for studying the dynamics ofcharged particles in complex electromagnetic őelds and has been successful in explaining particle energization in turbulent plasmas. However, this approach is fundamentally not self-consistent, as test particles do not generate their own electromagnetic fields and therefore do not interact with their surroundings realistically. In this work, we compare the energization of a population of test protons in a magnetofluid to that of a plasma composed of self-consistent particles. We use a compressible Hall magnetohydrodynamic (CHMHD) model for the test particle case and a hybrid particle-in-cell (HPIC) approach for the self-consistent case, conducting both 2D and 3D simulations. We calculate the rate of energization and conversion to thermal energy in both models, finding a higher temperature for the test particle case. Additionally, we examine the distribution of suprathermal particles and őnd that, in the test particle scenario, these particles eventually occupy the entire domain, while in the self-consistent case, suprathermal particles are confined to specific regions. We conclude that while test particles capture some qualitative features of their self-consistentcounterparts, they miss finer phenomena and tend to overestimate energization.